The Influence of Hadiths and Islamic Scholars’ Opinions on Current Miswak Practice - Ahmad Zharif Ibrahim; Nor Haliza Mat Baharin; Nurul Munirah Asa; Haslinda Ramli (USIM Press, 2024)
Vol. 5 No. 1 (2020): Jurnal Sains Insani